Diagnostic Performance of IOTA-SRs and RMI 4 For Diagnosis of Malignancy in Ovarian Masses Comparison with Histopathology - Jabin, Ishrat; Akter, Shahena; Hamid, Ayinur Nahar; Meher, Subrina; Akter, Tasrina; Begum, Hosne Ara; Chowdhury, Ireen (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: The discrimination between benign and malignant ovarian masses is essential for clinical management and surgical planning. This study aimed to compare the International Ovarian Tumor Analysis (IOTA) Simple Rules (SRs) and Risk of Malignancy Index (RMI) 4 as a diagnostic method to preoperative evaluation of malignant ovarian tumours by correlating with the postoperative histopathology reports. Materials and methods: This prospective observational study was conducted in the Obstetrics & Gynecology Department of Chittagong Medical College Hospital, Chattogram. 45 women with ovarian masses were included. Ultrasound examinations were performed. Demographic data and preoperative CA 125 levels were recorded. IOTA SRs and RMI-4 scoring were applied to predict malignancy. The final diagnosis was based on the histopathological diagnosis. Diagnostic accuracy in terms of sensitivity, specificity, Positive Predictive Value (PPV) Negative Predictive Value (NPV) and accuracy of each predictive tool was compared. Results: There were 28 (62.2%) subjects with benign tumours and 17 (37.8%) subjects with malignant tumours. The sensitivity, specificity, PPV, NPV and accuracy for the IOTA SRs were 94.1%, 92.9%, 88.9%, 96.3% and 93.3% respectively. For the RMI 4, with a cut-off value of 450 these were 52.9%, 85.7%, 69.2%, 75.0% and 73.3% respectively. Conclusion: IOTA SRs had higher diagnostic accuracy than RMI 4 to discriminate benign and malignant ovarian masses preoperatively. JCMCTA 2022 ; 33 (2) : 30-36